The Media and Social Networks as factors in the ‘Colour Revolutions’ - Nuraddın Mehdıyev (Technium Social Sciences Journal, 2020)
The purpose of this paper is to determine the roles and influence of the media and social networks on the ‘Colour Revolutions’ and to analyze the research conducted into them. The following methods were employed in the production of this research paper: analysis, synthesis, analogy, deduction, statistical analysis and comparative analysis. Novel in the article is the author’s comparison of the research and existing facts concerning the role of the media and social networks in the ‘Colour Revolutions’, while also attempting to define the essence of those events and systematically revealing the role of the media and social networks in their occurrence. The finding here is that the media, social networks, blogs and video hosting played a key role in the progress of the ‘Colour Revolutions’. During the first wave in the post-Soviet space, the principal agencies of influence were the traditional media (television and print). There was freedom of the media in Georgia, Ukraine and Kyrgyzstan as the ‘Colour Revolutions’ broke out in those countries (2003-2005). On the eve of those ‘revolutions’ that freedom allowed opposition forces to raise significantly their capacities to influence. The West also implemented its modern strategy of exerting ‘soft power’ via ICT across international politics. The Arab Spring saw parties in opposition relying on the new Internet media. The ruling regimes were unprepared for those challenges and lost the struggle for power. However, one of the main reasons for their defeat was their people’s dissatisfaction with the political-legal and socio-economic regimes they had established. The major powers, largely in control of ICT facilities, used those situations for their own purposes. If the West had not implemented its ‘soft power’ strategy via ICT in the post-Soviet and Middle East zones, the ‘revolutions’ would have been much less likely. Clear evidence of this can be seen in the example of the Gulf countries, which are of interest to the West for their energy resources.